Cognitive decline in U.S. military veterans: risk factors and clinical implications - MacLennan, Rob J.; Chapin, Benjamin A.; Solberg, Laurence M.; Clark, David J. (Frontiers in Dementia, 2026)
Military veterans have higher aggregate prevalence of risk factors for cognitive decline than non-veterans. This includes risk factors like diabetes, chronic pain, smoking, depression, and more. The disparity in prevalences is due in part to the unique experiences and exposures of their military service. Alzheimer's disease and other dementias are debilitating diseases with large financial and logistical burdens. These burdens are held by the patient, their family, friends, and caregivers, as well as healthcare professionals, and healthcare systems. Standardized screening for these risk factors may be helpful for understanding risk profiles that lead to cognitive decline. Additionally, screening must occur early to encourage early intervention and behavioral modifications and to reduce these burdens. This perspective presents the prevalence of risk factors for cognitive decline in the Veteran and non-veteran populations and proposes an approach to managing risk factors in Veterans.